Pengaruh Kecerdasan Emosional Terhadap Kinerja Guru SMK Negeri 1 Bintan Timur - Yayuk Sri Mulyani Rahayu (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The aims of this study were (1) to determine the extent of emotional intelligence at SMK Negeri 1 Bintan Timur, (2) to determine the performance of teachers at SMK Negeri 1 Bintan Timur, and (3) to determine the effect of emotional intelligence on teacher performance at SMK Negeri 1 Bintan. East. This research has a quantitative approach, using regression data analysis techniques. The research location is SMK Negeri 1 Bintan Timur, with a sample size of 47 people. Data was collected using techniques and instruments in the form of questionnaires and tests. The results of the analysis show that the emotional intelligence of teachers at SMK Negeri 1 Bintan Timur is good, the performance of teachers at SMK Negeri 1 Bintan Timur is said to be good, there is an influence between emotional intelligence and teacher performance at SMK Negeri 1 Bintan Timur.